2021
DOI: 10.1101/2021.10.25.21265466
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

An externally validated deep learning model for the accurate segmentation of the lumbar paravertebral muscles

Abstract: Purpose. Imaging studies about the relevance of muscles in spinal disorders, and sarcopenia in general, require the segmentation of the muscles in the images which is very labour-intensive if performed manually and poses a practical limit to the number of investigated subjects. This study aimed at developing a deep learning-based tool able to fully automatically perform an accurate segmentation of the lumbar muscles in axial MRI scans, and at validating the new tool on an external dataset. Methods. A set of 60… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…In clinical practice, LBP refers to the lower back, lumbosacral, hip pain as the main manifestation of a syndrome.Surveys show that 80% of adults will have LBP at different times in their life, with an incidence of 7.6% to 37%. For people under 45 years old, non-speci c LBP is the main cause of limited activity [29] .Previous studies [30][31][32][33][34] have indicated that there is a close relationship between the paravertebral muscle and non-speci c LBP.Since paravertebral muscles play a leading role in the stability of the spine, paravertebral muscle atrophy and muscle ber characteristics changes caused by the fear of movement and protective posture of patients with chronic LBP are often regarded as the main reasons for recurrent episodes of chronic LBP.Our study showed that the total FIR in LBP group and LDH group was higher than that in normal group. The higher the VAS score and ODI score in the LBP group and the LDH group, the higher the FIR.This also con rmed that patients in the LBP group and the LDH group were related to the FIR in the parathyteal muscle, and the greater the FIR, the greater the lumbago.…”
Section: Discussionmentioning
confidence: 99%
“…In clinical practice, LBP refers to the lower back, lumbosacral, hip pain as the main manifestation of a syndrome.Surveys show that 80% of adults will have LBP at different times in their life, with an incidence of 7.6% to 37%. For people under 45 years old, non-speci c LBP is the main cause of limited activity [29] .Previous studies [30][31][32][33][34] have indicated that there is a close relationship between the paravertebral muscle and non-speci c LBP.Since paravertebral muscles play a leading role in the stability of the spine, paravertebral muscle atrophy and muscle ber characteristics changes caused by the fear of movement and protective posture of patients with chronic LBP are often regarded as the main reasons for recurrent episodes of chronic LBP.Our study showed that the total FIR in LBP group and LDH group was higher than that in normal group. The higher the VAS score and ODI score in the LBP group and the LDH group, the higher the FIR.This also con rmed that patients in the LBP group and the LDH group were related to the FIR in the parathyteal muscle, and the greater the FIR, the greater the lumbago.…”
Section: Discussionmentioning
confidence: 99%
“…Automatic tissue segmentation from MRI data showcases the ability of machine learning to perform complex tasks, such as vertebrae recognition and segmentation with a high degree of accuracy, comparable to manual segmentation by physicians (56,57,58). Attention has also been devoted to the segmentation of paravertebral muscles (59,60,61), the properties of which (such as cross-sectional areas and fatty infiltration) are known to be associated with disability and treatment outcomes (62).…”
Section: Imagingmentioning
confidence: 99%